Budaya Salam Sapa Sebagai Manifestasi Sila Ketiga Pancasila : (Studi Pada Interaksi Sosial Di Fakultas Ilmu Sosial Unimed) - Griyani Elisabeth Purba; Nike Margaretha Br Sembiring; Rani Oktavia Purba; Tessa Lonika Simanullang (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
In research conducted at the Unimed Faculty of Social Sciences, the culture of greetings as a manifestation of the Third Principle of Pancasila was investigated. The culture of greetings is a form of social interaction that involves the use of greetings or greetings when communicating with other people. This research aims to understand how the greeting culture is implemented in social interactions at the Unimed Faculty of Social Sciences. In the context of Pancasila, the Third Principle "Indonesian Unity" emphasizes the importance of unity and oneness in national and state life. The culture of greetings and greetings can be considered as a manifestation of this Third Principle, because through greetings, people can acknowledge each other's existence and presence, as well as strengthen the sense of unity and oneness as the Indonesian nation. This research involves the study of social interactions at the Unimed Faculty of Social Sciences, which is an academic environment where students and faculty staff interact with each other. In this research, researchers analyze how the culture of greetings and greetings is implemented in daily interactions at the faculty. The results of this research can provide a better understanding of how the culture of greetings and greetings can be a manifestation of the Third Principle of Pancasila in social life at the Unimed Faculty of Social Sciences.